Correlation of Contact Sensitization to Common Allergens with Disease Severity in Discoid Eczema: An Analytical Observational Study - Aishwarya Raheja; Ajay Kumar; Avinash Jadhav; Mahendra Singh Deora; Dipti Mathias; Prachi Agrawal; Rahul Ranpariya (Wolters Kluwer Medknow Publications, 2022)
Background: Discoid eczema, defined by well-demarcated round or oval plaques, is a form of endogenous eczema in which the role of contact allergens is not clearly established. Objectives: This study aims to assess the role of contact allergens in discoid eczema by patch testing, determine clinical relevance and correlate patch test reactivity with the severity of disease and atopy. Materials and Methods: Sample characteristics including occupation, atopic diathesis and clinical details were recorded. Disease severity was assessed by the Eczema and Area Severity Index (EASI) and patch testing carried out with the Indian Standard Battery. Relevance of patch tests was determined by a history of exposure and patch testing with patients' own materials. Results: Fifty-one patients having a median age of 38 years were enrolled out of which 31 (60.8%) were male. Patch tests were reactive in 25 (49%) patients, common sensitizers being fragrance mix in 9 (31.0%), potassium dichromate in 4 (13.8%), paraphenylenediamine in 4 (13.8%), and nickel in 3 (10.3%) cases. Clinical relevance was established in 11 (37.9%) cases. In patch test reactive patients the mean EASI score was 3.4 as compared with 4.5 in nonreactors. Patch tests were positive in 3 (25%) atopic as compared with 22 (56.4%) nonatopic patients. Conclusion: Contact sensitization to common allergens may not contribute to disease severity in discoid eczema. Patch test reactivity is low in atopic as compared with nonatopic patients with discoid eczema.